Predictive value of bile acids as metabolite biomarkers for gallstone disease: A systematic review and meta-analysis - Han, Xu; Wang, Juan; Wu, Yingnan; Gu, Hao; Zhao, Ning; Liao, Xing; Jiang, Miao (PloS one, 2024)
The profiles of bile acids (BAs) in patients with gallstone disease (GSD) have been found to be altered markedly though in an inconsistent pattern. This study aims to characterize the variation of the BA profiles in GSD patients, thereby to discover the potential metabolite biomarkers for earlier detection of GSD. Literature search of eight electronic database in both English and Chinese was completed on May 11, 2023. The qualitative and quantitative reviews were performed to summarize the changes of BA profiles in GSD patients compared with healthy subjects. The concentrations of BAs were adopted as the primary outcomes and the weighted mean differences (WMDs) and 95% confidence interval (CI) were generated by random-effects meta-analysis models. A total of 30 studies were enrolled which included 2313 participants and reported the 39 BAs or their ratios. Qualitative review demonstrated serum Taurocholic Acid (TCA), Glycochenodeoxycholic acid (GCDCA), Glycocholic acid (GCA), Taurochenodeoxycholic acid (TCDCA), Glycodeoxycholic acid (GDCA) and Deoxycholic acid (DCA) were significantly increased in GSD patients compared with healthy subjects. Meta analysis was performed in 16 studies and showed that serum Total BAs (TBA) (WMD = 1.36μmol/L, 95%CI = 0.33; 2.4) was elevated however bile TBA (WMD = -36.96mmol/L, 95%CI = -52.32; -21.6) was declined in GSD patients. GCA (WMD = 0.83μmol/L, 95%CI = 0.06; 1.6) and TCA (WMD = 0.51μmol/L; 95%CI = 0.18; 0.85) were both increased in serum sample; TCDCA (WMD = 2.64mmol/L, 95%CI = 0.16; 5.12) was rising, however GCDCA (WMD = -13.82mmol/L, 95%CI = -21.86; -5.78) was falling in bile sample of GSD patients. The level of serum DCA in the GSD patients was found to be increased by using chromatography, yet decreased by chromatography mass spectrometry. The profiles of BAs demonstrated distinctive changes in GSD patients compared with healthy control subjects. Serum GCA, TCA and GCDCA, as the typically variant BAs, presented as a potential marker for earlier diagnosis of GSD, which could facilitate early prophylactic intervention. Yet, further validation of these biomarkers by longitudinal studies is still warranted in the future. PROSPERO registration number CRD42022339649.